2009
DOI: 10.1111/j.1740-8709.2008.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Women's experiences of infant feeding support in the first 6 weeks post‐birth

Abstract: Research suggests women find the first 2 to 6 weeks to be the most difficult time for breastfeeding. It has been identified that women need and seek support with breastfeeding during this time. Support is a difficult concept to define. When discussed by professionals, support for breastfeeding is generally viewed in terms of providing information and educational interventions. There is little understanding of the different elements of breastfeeding support strategies and the mechanisms by which support operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 40 publications
2
50
0
1
Order By: Relevance
“…Other key areas of concern related to occasions where volunteers were unable to answer the callers’ questions or callers receiving what they considered to be judgmental attitudes. The need for non-judgmental attitudes and support in caring for new mothers is well reported in the literature [30,32]. On occasions when follow-up support is warranted, or required by callers, call-back services could be provided by the volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Other key areas of concern related to occasions where volunteers were unable to answer the callers’ questions or callers receiving what they considered to be judgmental attitudes. The need for non-judgmental attitudes and support in caring for new mothers is well reported in the literature [30,32]. On occasions when follow-up support is warranted, or required by callers, call-back services could be provided by the volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, the WHO and UNICEF (2009) launched the Baby-friendly Hospital Initiative (BFHI) [hereafter called BFI] model of care to promote, support, and protect breastfeeding in health institutions and community settings. There is a need to better understand the experiences of mothers exposed to BFI services, as it is presented worldwide as the gold standard model of care to promote and support breastfeeding (Sheehan, Schmied, & Barclay, 2009;McInnes & Chambers, 2008). There is a need to better understand the experiences of mothers exposed to BFI services, as it is presented worldwide as the gold standard model of care to promote and support breastfeeding (Sheehan, Schmied, & Barclay, 2009;McInnes & Chambers, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Midwives provide antenatal, labour and postnatal care. Once a woman is discharged from hospital, postnatal care is provided by the GP and public health nursing service.Research has shown that women face different issues when breast-feeding such as not being adequately prepared for breast-feeding (4,5) , feeling embarrassed about breast-feeding in public (6)(7)(8) , perceiving insufficient milk supply (9,10) and receiving conflicting advice that subsequently undermines their confidence (11,12) . In addition, breast-feeding has been described as a 'problematic social act' whereby women try and find a balance between the act of breast-feeding and the needs, expectations and comfort of others (13) .…”
mentioning
confidence: 99%